PALEOMAGNETIC ANALYSIS OF NEOTECTONIC DEFORMATION IN THE ANATOLIAN ACCRETIONARY COLLAGE, TURKEY - Piper J.D.A.; Tatar O.; Gursoy H.; Koçbulut F.; Mesci B.L. (My University, 2006)
Closure of the Neo-Tethyan Ocean in the Turkish sector of the Alpine-Himalayan orogen by ca. 12 Ma was succeeded by deformation of a domain between the Eurasia plate, presently bounded by the North Anatolian fault, and the Arabian indenter. Facets of this deformation comprise the crustal thickening and uplift that produced the Anatolian plateau, the establishment of transform faults, and tectonic escape as Arabia has continued to impinge into the collage of Anatolian terranes accreted by closure of the Neo-Tethys. We have compiled a database of neotectonic paleomagnetic results from Anatolia to analyze this deformation. Large rotations (up to 5°/10,000 yr) of small fault blocks along the intracontinental transform faults but do not extend away from these zones and show that seismogenic upper crust is decoupled from lower continental lithosphere undergoing continuum deformation. Between the transforms, large fault blocks exhibit slower rotation rates (mostly <1°/100,000 yr), varying systematically across Anatolia. Large counterclockwise rotations near the Arabian indenter diminish westward, becoming zero, and then move clockwise near the limit of tectonic escape. The view that the collage has rotated counterclockwise as a single plate, either uniformly or episodically, during the Neotectonic era is refuted. Instead, deformation has been distributed and differential as the collage adapted to changing tectonic regimes. Crustal extrusion to the west and south has expanded the curvature of the Tauride arc and combined with back-roll on the Hellenic arc to produce the extensional horst and graben province in western Turkey. The latitudinal motions are close to confidence limits but consistent with ̃800 km of northward motion of Anatolian terranes over 40 m.y., a figure including up to a few hundred kilometers of closure linked to crustal thickening since the demise of the Neo-Tethys. © 2006 Geological Society of America.
Keywords: AEGEAN; ANATOLIA; INCLINATION ANOMALY; NEOTECTONICS; PALEOMAGNETISM; TECTONIC ESCAPE; TECTONIC ROTATION; TURKEY